Propiedades mecánicas, eléctricas y de durabilidad de concretos con agregados reciclados (2017)
The purpose of this article is to present the assessment of some of the electrical, mechanical and durability properties of concrete mixtures with replacement of coarse aggregate by aggregates of recycled concrete (ACR). The ACR used in the mixtures of the tests was produced from the crushing of concrete specimens, which had been tested in the laboratory of the Colombian School of Engineering. Eight mixtures with four contents of recycled aggregates (0%, 25%, 50% and 100%) and two values ​​of water / cement ratio (0.5 and 0.6) were evaluated. Among the properties analyzed are the compression resistance, modulus of elasticity, resistivity, impedance, ultrasonic pulse velocity, permeability to the chloride ion, carbonation and thickeness. The results of the tests clearly indicated that in the mixtures with the highest percentage of recycled aggregate, the results of the modulus of elasticity and the resistance to compression are lower than for concretes with natural aggregate. The resistance to compression of a concrete with 100% ACR has an estimated reduction of 20 to 25%, with respect to a conventional concrete. At the same time, the electrical properties and the durability measured by resistivity, impedance, permeability and chloride ion permeability, and sorptivity tests are affected by the increase in the percentage of recycled aggregate and the water / cement ratio.